PERILAKU MANAJEMEN KEUANGAN KARYAWAN SELAMA PANDEMI COVID-19: SEBUAH STUDI AWAL - Zulmi Ramdani; Andi Amri; Jaka Warsihna; Titi Ratna Garnasih; Eka Juarsa (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
The COVID-19 pandemic has brought many changes to various aspects of the lives of employees in the world, especially Indonesia. The economic aspect is considered to be one of the factors that have been affected by the pandemic. This certainly affects the financial management behaviour of affected employees. This study aims to explore the financial management behaviour of a number of employees who have experienced the impact of the COVID-19 technique. The 8 respondents were selected using purposive sampling technique. Thematic content analysis is used to identify respondent’s answers through an online interview process. The results show that there are differences in financial management behaviour between those who are permanent employees and those in position as contract employees. The existing employment status has an influence on the financial behaviour of employees. In addition, employee psychological factors also play a role in strengthening employee readiness to face work dynamics during the COVID-19 pandemic. The results and recommendations of this initial study will be discussed further in this article.